Genesis : the evolution of biology - Sapp, Jan (Oxford University Press, 2003)
What is evolution? What is a gene? How did these concepts originate and how did they develop? This book is a short history ranging from Lamarck and Darwin to DNA and the Human Genome Project, exploring the conceptual oppositions, techniques, institutional conditions and controversies that have shaped the development of biology.